Positive Side Effects? The Impact of Populist Radical Right Parties in Government on the Media Visibility of the Austrian Parliament. Issue 4 (12th March 2021) - Miklin, Eric; Dolezal, Martin
Abstract: This article takes up the scholarly debate on the relationship between populism and democracy and analyses the effect populist radical right parties (PRRPs) in government have had on the representative function of the Austrian parliament . Building on insights from theories of newsworthiness, we expect these parties to positively affect the visibility of parliament due to the increased conflict between governing and mainstream opposition parties, thereby increasing parliamentary accountability. Our analysis covers the period from 1994 to 2020, with PRRPs in government from 2000 to 2007 and again from 2017 to 2019. Empirical inference is based on the weekly coverage of the Austrian parliament's first chamber ( Nationalrat ) in a sample of four daily newspapers. The findings show that the first term in government did indeed have a positive and significant effect on media coverage. However, that this effect is not found for the second term suggests that its existence and size depend on the concrete political circumstances under which governments and media outlets operate.